Explicit Dynamic Frontal Crash Analysis of an All-Terrain Vehicle Roll Cage - Mittal, Ashwani; Mahato, Anil C.; Sharma, Mukesh; Mukhopadhyay, Arkadeb; Kadian, Arun Kumar (Applications of Modelling and Simulation, 2023)
This work deals with the explicit dynamic frontal crash analysis of the roll cage of an All-Terrain Vehicle. The crash testing analysis is done to ensure the safety of the driver during an accident in a catastrophic event. A roll cage model of the All-Terrain Vehicle is developed as per the rules laid down by BAJA SAE INDIA for m-BAJA vehicles using SolidWorks. Thereafter, the dynamic frontal crash analysis is performed by making a collision with a rigid wall, keeping a uniform velocity of the roll cage is 40 km/h. The analysis is carried out in HyperWorks software using Radioss solver. The work established the driver safety for the proposed roll cage by analyzing the stress development, and the total deformation after the collision. It is found that Von Mises stresses of the roll cage model except a joint of Side Impact Member is lower than the permissible limit.